2018
DOI: 10.1080/01443615.2018.1443060
|View full text |Cite
|
Sign up to set email alerts
|

Survey on knowledge, attitude, acceptance and related factors among pregnant women in Thailand regarding antenatal thalassaemia screening

Abstract: Thalassaemia is a common haematologic health condition in Southeast Asian countries (SEA) including Thailand. Reducing the birth of new thalassaemia cases is an effective method to control disease. The background level of knowledge and attitude of pregnant women on the disease influences their decision to perform antenatal screening. Unfortunately, the information about pregnant women's knowledge and attitude on antenatal thalassaemia screening in a developing country such as Thailand is lacking. We therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Despite thalassemia being one of the most commonly screened‐for conditions internationally (Cousens et al, 2010), few studies have explored the views of thalassemia‐affected families and screen‐identified carriers. Most studies have focused on the views of pregnant women from the general population (Tsianakas, Atkin, Calnan, Dormandy, & Marteau, 2012) and/or at‐risk ethnic minority groups (Ahmed, Green, & Hewison, 2006; Atkin, Ahmed, Hewison, & Green, 2008; Darr et al, 2013; Hanprasertpong et al, 2018), to whom thalassemia screening is targetted. Nevertheless, the accounts of affected families, adults, and carriers offer important insights into the daily realities of life with thalassemia as well as the experience of receiving, and responding, to screen‐positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Despite thalassemia being one of the most commonly screened‐for conditions internationally (Cousens et al, 2010), few studies have explored the views of thalassemia‐affected families and screen‐identified carriers. Most studies have focused on the views of pregnant women from the general population (Tsianakas, Atkin, Calnan, Dormandy, & Marteau, 2012) and/or at‐risk ethnic minority groups (Ahmed, Green, & Hewison, 2006; Atkin, Ahmed, Hewison, & Green, 2008; Darr et al, 2013; Hanprasertpong et al, 2018), to whom thalassemia screening is targetted. Nevertheless, the accounts of affected families, adults, and carriers offer important insights into the daily realities of life with thalassemia as well as the experience of receiving, and responding, to screen‐positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors affect the knowledge of transmission of disease and option of preventive services. A study conducted in Thailand showed that lack of maternal awareness related to antenatal screening is related to age, education, multi-gravidity and family history of thalassemia 11. A study conducted in Pakistan assessed that only 33% of the parents of thalassemic children had knowledge about premarital screening for detection of thalassemia trait and 76.5% had knowledge of prenatal screening 12.…”
Section: Introductionmentioning
confidence: 99%